2022
DOI: 10.1093/mnras/stac245
|View full text |Cite
|
Sign up to set email alerts
|

Starquakes in millisecond pulsars and gravitational waves emission

Abstract: So far, only transient Gravitational waves (GWs) produced by catastrophic events of extra-galactic origin have been detected. However, it is generally believed that there should be also continuous sources of GWs within our galaxy, such as accreting neutron stars (NSs), that could in principle be detected in the next near future. In fact, in these objects, centrifugal forces can be so strong to break the neutron star crust (causing a starquake), thus producing a quadrupole moment responsible for the continuous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…It found that τ sd is longer than τ p by a factor of 4.21, indicating that the decreases of Ω p is faster than Ω s . Note that ǫ depends on the deformation of a newborn magnetar, which is mainly induced by its magnetic field and starquake (Mastrano et al 2018;Giliberti & Cambiotti 2022). The change of the magnetic field can be ignored in the early stage since its decay timescale is relatively long, and the deformation induced by the magnetic field can be regarded as a constant in the early stage (Turolla et al 2015).…”
Section: Precession Evolution Of the Magnetarmentioning
confidence: 99%
“…It found that τ sd is longer than τ p by a factor of 4.21, indicating that the decreases of Ω p is faster than Ω s . Note that ǫ depends on the deformation of a newborn magnetar, which is mainly induced by its magnetic field and starquake (Mastrano et al 2018;Giliberti & Cambiotti 2022). The change of the magnetic field can be ignored in the early stage since its decay timescale is relatively long, and the deformation induced by the magnetic field can be regarded as a constant in the early stage (Turolla et al 2015).…”
Section: Precession Evolution Of the Magnetarmentioning
confidence: 99%
“…It is worth noting that the value of σ max is very uncertain. Reference [14] adopted a larger breaking strain σ max = 10 −1 , and found that the breaking frequency is in the range 200 − 600 Hz for a typical M = 1.4M of NS, while σ max = 10 −5 is adopted by [48], and found that the fracture frequency would be about two orders of magnitude smaller than that of 200 − 600 Hz. It means that the crust of the neutron star will be fractured when we change the frequency a little bit (a few Hz).…”
Section: B Starquake-induced Ellipticitymentioning
confidence: 99%
“…To date, many deformation mechanisms that enable an isolated system to emit GWs have been proposed in the literature [13][14][15][16][17][18][19]. Magnetars are generally believed to have strong magnetic fields [20][21][22][23][24][25][26], and the magnetic stress is too large for the magnetar to maintain a longlasting spherical structure [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations